Review of information technologies and their importance in the educational directory of education - Ivanov, A.V. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2018)
The article focuses on the fact that the need for education is continuous and ongoing process therefore anytime anywhere access to it is becoming a necessity. The need for information is constantly increasing phenomenon. Education should meet the needs of different groups of learners, and therefore, modern information technologies are important to meet this need. Discusses the requirements of society, which consist in the fact that all the members of this society have the necessary level of technological literacy. Thus, increasing access and reducing the cost of education with the aim of achieving the planned quality of education possible to implement cloud-based IT technologies. Sets out the specifics of cloud computing, which imposes special requirements for training in their use, including the management of educational process. Draws conclusions about what information and communication technologies, understanding the capabilities of cloud technologies and their impact on the management efficiency of the education system, are the main prerequisites for the development of professional competence of the head of the educational organization in the field of information technology.